ANALISIS WACANA KRITIS SARA MILLS PADA BERITA PRIA DI WONOGIRI PERKOSA DUA ANAK TIRINYA SALAH SATU KORBAN MELAHIRKAN BAYINYA - Luqman Karim Yogaswara; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
This research discusses two girls who were raped by their stepfather until one of the victims gave birth in online media reports. Various reports regarding sexual harassment often experienced by women represent a person in a discourse. This research uses the Sara Mills model of critical discourse analysis theory which focuses on women's issues such as how women are presented in texts, images, photos and in the news. This research aims to describe the discourse analysis of the case of two children who were raped by their stepfather in online news from Sara Mills' perspective (Bkompas.com media reporting study). The method used is descriptive qualitative, with data collection techniques namely reading techniques and note-taking techniques. In this research, it was found that in the subject position in the two news stories about the case of two children being raped by their stepfather was a father who had the heart to rape his two children until one of them gave birth, then in the object position were both teenage children. one is 14 years old and his older brother is 17 years old. Then, in the writer's position, namely the Kompas.com news journalist who describes the story very clearly but briefly and concisely. Describes the flow of events and the background of the perpetrator and victim and gives voice to the heart of a woman who has been harassed. Lastly, the reader's position is to show that those who consume the news are men because they have difficulty controlling their own desires. Keywords: Sara Mills, Critical Discourse, Online News